Corporate Governance Evaluation of PT Bank A in Relation with Spin-Off Preparation Sharia Business Units - Nugroho, Arief; Violita, Evony Silvino (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The motivation for the research is due to Bank A prepared for a Spin-Off Sharia Business Unit to comply with the provisions of Law No 21 of 2008 relating to Islamic banking, there are several cases regarding corporate governance in Sharia banking, so Bank A has an obligation to make sure current practice of corporate governance is adequate enough to be benchmarked by Sharia Business Unit. The goal of the research is to evaluate the practice of corporate governance in PT Bank A in relation to the Spin-Off preparation Sharia Business Unit to comply with the provisions of Law No. 21 of 2008 relating to Islamic Banking. The evaluation has become important because Bank A has responsibilities to guide the corporate governance design of the Sharia Business Unit to be a separate entity using the current corporate governance practice of Bank A as a benchmark. Document analysis and a semi-structured face-to-face procedure interview were employed to achieve the purposes of the research. Data were taken from the Head of Corporate Secretary, Financial Controller, Sharia Planning and Strategic Head, and internal documents of PT Bank A. There are several aspects of Bank A to improve in order to have a better corporate governance foundation to guide the preparation process for establishing (spin-off) Sharia Business Units such as strengthening of systems, infrastructure, and public participation processes. This study adds to the knowledge body on the evaluation of corporate governance for conventional banking in order to spin off Sharia business units due to the obligation stated in the provisions of Law No. 21 of 2008 relating to Islamic Banking. The study also argued not only the regulation can be used as an indicator for evaluation but using the “beyond regulation” indicator will be beneficial to improve current corporate governance practices to become efficient and effective. This research is going to evaluate the corporate governance practice of PT Bank A using the General Guidelines for Governance of Indonesian Sharia Entities (Pedoman Umum Governansi Entitas Syariah Indonesia) (PUG-ESI) which the guideline is new in Indonesia. This research is going to give an overview of the current implementation of corporate governance and the steps that need to be taken to prepare for a spin-off in 2023 in terms of complying with corporate governance guidance. This research can be used as a good benchmark for the conventional banking industry which spin-offs Sharia Business Units in Indonesia.